Ileostomy After Intestinal Transplantation: The First in Depth Report on Techniques, Complications, and Outcomes. Issue 3 (March 2020) - Dumronggittigule, Wethit; Venick, Robert S.; Dubray, B. John; Cheng, Elaine C.; Duffy, John P.; Marcus, Elizabeth A.; Busuttil, Ronald W.; Farmer, Douglas G.
Abstract : Background: Temporary ileostomy during intestinal transplantation (ITx) is the standard technique for allograft monitoring. A detailed analysis of the ITx ileostomy has never been reported. Methods: A retrospective review of a single-center ITx database was performed. The analysis was divided into ileostomy formation and takedown episodes. Results: One hundred thirty-five grafts underwent ileostomy formation, and 79 underwent ileostomy takedown. Median age at ITx was 7.7 years and weight was 23 kg. Allograft types were intestine (22%), liver/intestine (55%), multivisceral (16%), and modified multivisceral (7%). Sixty-four percent had 1-stage ITx, whereas 36% required 2-staged ITx. Final ileostomy types were end (20%), loop (10%), distal blowhole (59%), and proximal blowhole (11%). Ileostomy formation: Thirty-one grafts had complications (23%), including prolapse (26%), ischemia (16%), and parastomal hernia (19%). Twelve required surgical revision. There were no significant differences in graft type, ileostomy type, survival, and ileostomy takedown rate between grafts with and without complications. Colon inclusive grafts had higher complication rates ( P = 0.002). Ileostomy takedown: Ileostomy takedown occurred at a median of 422 days post-ITx. Twenty-five complications occurred after 22 takedowns (28%), including small bowel obstruction (27%) and abscess (18%). Fifteen grafts required surgical correction. Recipients with complications had longer hospital stay (17 versus 9 d; P = 0.001) than those without complications. Graft type, ileostomy type, and survival were not different. Conclusions: The first of its kind analysis of the surgical ileostomy after ITx reveals that most recipients can undergo successful ileostomy formation/takedown, complication rates are significant but within an acceptable range, and complications do not affect survival. This study demonstrates that the routine use of transplant ostomies remains an acceptable practice after ITx. However, true analysis of risk and benefit will require a randomized control trial.